Prosody development for Filipino text-to-speech systems - Co, Melvin O. (2002)
Prosody is the aspect of speech that gives linguistic information at a suprasegmental level, which aids in the comprehension and intelligibility of the speech. Prosody is composed of the microprosodic component and macroprosodic component. Microprosody is influence by individual speech sounds while macroprosody is a speaker's choice of intonation. In this research, an automated macroprosody overlay for Filipino Text-to-Speech (TTS) system was developed. Samples of selected natural utterances of Filipino sentences was collected, pre-processed, transcribed at the word level and analyzed for macroprosody of continuous speech. In addition, isolated utterance of Filipino words as gathered, which serves as the speech corpus for the TTS system. When a sentence or phrase is typed, utterance of each word is obtained from the speech corpus. In order for the synthesized speech to sound natural, appropriate pitch and duration obtained from the gathered Filipino sentences are applied through the use of a concatenative synthesizer called Time Domain Pitch Synchronous Overlap-add (TD-PSOLA) technique. Acceptability test show that the Filipino TTS system comparable to some commercially available English TTS systems. Furthermore, Declarative/Interrogative test confirms that macroprosody was captured by the synthesized speech.
Thesis (M.S. Electrical Engineering)--University of the Philippines, Diliman.
Keywords: Filipino language -- Versification -- Automation; Speech processing systems; Speech synthesis